A MgFe‐LDH Nanosheet‐Incorporated Smart Thermo‐Responsive Hydrogel with Controllable Growth Factor Releasing Capability for Bone Regeneration. Issue 5 (19th December 2022) - Lv, Zehui; Hu, Tingting; Bian, Yixin; Wang, Guanyun; Wu, Zhikang; Li, Hai; Liu, Xueyan; Yang, Shuqing; Tan, Chaoliang; Liang, Ruizheng; Weng, Xisheng
Abstract: Although growth factor (GF)‐loaded hydrogels have been explored as promising materials in repairing bone defects, it still remains challenging to construct smart hydrogels with excellent gelation/mechanical properties as well as controllable GF releasing capability. Herein, the incorporation of bone morphogenetic protein 2 (BMP‐2)‐functionalized MgFe‐layered double hydroxide (LDH) nanosheets into chitosan/silk fibroin (CS) hydrogels loaded with platelet‐derived growth factor‐BB (PDGF‐BB) to construct a smart injectable thermo‐responsive hydrogel (denoted as CSP‐LB), which can achieve a burst release of PDGF‐BB and a sustained release of BMP‐2, for highly efficient bone regeneration is reported. The incorporation of MgFe‐LDH in CS hydrogel not only shortens the gelation time and decreases sol–gel transition temperature, but also enhances the mechanical property of the hydrogel. Because of the sequential release of dual‐GFs and sustained release of bioactive Mg 2+ /Fe 3+ ions, the in vitro experiments prove that the CSP‐LB hydrogel exhibits excellent angiogenic and osteogenic properties compared with the CS hydrogel. In vivo experiments further prove that the CSP‐LB hydrogel can significantly enhance bone regeneration with higher bone volume and mineral density than that of the CS hydrogel. This smart thermo‐sensitive CSP‐LB hydrogel possesses excellent gelation capability and angiogenic and osteogenic properties, thus providing a promising minimally invasive solution for bone defect treatment. Abstract : A smart injectable thermo‐responsive hydrogel composed of bone morphogenetic protein 2‐functionalized MgFe‐layered double hydroxide nanosheets and platelet‐derived growth factor‐BB‐loaded chitosan/silk fibroin hydrogel is designed and constructed to achieve the sequential release of dual growth factors and sustained release of bioactive Mg 2+ /Fe 3+ ions for highly efficient bone regeneration.